2008
DOI: 10.2134/agronj2006.0153
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Chlorophyll Meters for Diagnosing Nitrogen Deficiencies of Corn in Production Agriculture

Abstract: A gronomy J our n al • Volume 10 0 , I s sue 3 • 2 0 0 8 543 ABSTRACT Chlorophyll meters have been widely used to diagnose N defi ciencies in research trials and to help refi ne N fertilizer recommendations in production agriculture. Th e diagnoses are based on the assumption that chlorophyll meters can detect a wide range of N defi ciencies under fi eld conditions according to relationships between chlorophyll meter readings (CMRs) and yield responses to N fertilization that are established from small-plot tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
2
34
1
2
Order By: Relevance
“…A minimal difference of SPAD readings in plants grown using the two NH 3 application directions is consistent with previous research results (Zhang et al, 2008a(Zhang et al, , 2009 where authors showed possible limitations of SPAD in identifying moderate N deficiencies; the N levels applied in this study (starter N fertilizer + 145 or 202 kg N ha -1 ) would not be expected to severely limit crop growth or N uptake. In addition, SPAD readings were taken from the ear-leaf where higher N concentrations are expected to persist longer during grain fill due to its proximity to the sink Bonhomme, 1999, 2004).…”
Section: In-season Observations and Measurementssupporting
confidence: 92%
“…A minimal difference of SPAD readings in plants grown using the two NH 3 application directions is consistent with previous research results (Zhang et al, 2008a(Zhang et al, , 2009 where authors showed possible limitations of SPAD in identifying moderate N deficiencies; the N levels applied in this study (starter N fertilizer + 145 or 202 kg N ha -1 ) would not be expected to severely limit crop growth or N uptake. In addition, SPAD readings were taken from the ear-leaf where higher N concentrations are expected to persist longer during grain fill due to its proximity to the sink Bonhomme, 1999, 2004).…”
Section: In-season Observations and Measurementssupporting
confidence: 92%
“…Chlorophyll meter readings for 10 ear leaves plot -1 were collected to determine N deficiency (Zhang et al, 2008) using a Minolta SPAD-502 (Konica Minolta Optics, Inc.) at VT (Abendroth et al, 2011). Ear leaves (10 plot -1 ) were collected at R1, dried, and analyzed for total N concentration by combustion using a total C:N analyzer (LECO, TruSPEC CN Analyzer, St. Joseph, MI).…”
Section: Soil Sampling and Field Measurementsmentioning
confidence: 99%
“…A produtividade de grãos de milho variou em consequência das doses de N aplicadas, nos três experimentos de campo, tendo-se obtido 6,9 Mg ha (Rambo et al, 2007b; (Sangoi et al, 2003;Ma et al, 2005;Zhang et al, 2008).…”
Section: Resultsunclassified